2016
DOI: 10.1016/j.jash.2015.11.013
|View full text |Cite
|
Sign up to set email alerts
|

Genetic predisposition in patients with hypertension and normal ejection fraction to oxidative stress

Abstract: The role of oxidative stress (OXS) due to myocardial nitric oxide synthase (NOS) uncoupling related to oxidative depletion of its cofactor tetrahydrobiopterin (BH 4 ) emerged in the pathogenesis of heart failure with preserved ejection fraction (HFPEF).We determined the prevalence of 6 single nucleotide polymorphisms (SNPs) of genes encoding enzymes related to OXS, BH 4 metabolism and NOS function in >60-year-old 94 patients with hypertension and 18 age-matched controls with normal EF. Using echocardiography 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…MTHFR , which encodes methylenetetrahydrofolate reductase, and SH2B3 , which regulates cell differentiation, may influence cellular redox states indirectly. Recent studies indicate a high genetic risk of oxidative stress in hypertensive patients, evidenced by increased prevalence of SNPs of genes encoding enzymes related to oxidative stress (guanosine triphosphate cyclohydrolase-1 involved in BH4 synthesis, mSOD and eNOS) (4). Together genes regulating vascular function and oxidative stress seem to track with hypertension.…”
mentioning
confidence: 99%
“…MTHFR , which encodes methylenetetrahydrofolate reductase, and SH2B3 , which regulates cell differentiation, may influence cellular redox states indirectly. Recent studies indicate a high genetic risk of oxidative stress in hypertensive patients, evidenced by increased prevalence of SNPs of genes encoding enzymes related to oxidative stress (guanosine triphosphate cyclohydrolase-1 involved in BH4 synthesis, mSOD and eNOS) (4). Together genes regulating vascular function and oxidative stress seem to track with hypertension.…”
mentioning
confidence: 99%
“…from the cytoplasm to the mitochondria, and β folding affected the proper identification of the signal peptides and related receptors on the mitochondrial inner membrane, and exhibited reduced the transcriptional activity of SOD2 to the mitochondria by 30-40% affect the entry of SOD2 into mitochondria to play an antioxidant role, which increased the risk of coronary artery disease [25].Mutations in the SOD2 gene increase the risk of developing cancer, SOD2 SNP rs4880 (T > C) resulted in conformational changes of the protein helix structure, an increased risk of oral cancer, and has been linked to a variety of others cancers [26]. Studies have shown that rs4880 SNP (T > C changes at the nucleotide level) at codon 16 causes alanine (GCT) to replace valine (GTT) [27].…”
Section: Hardy-weinberg Balance Analysismentioning
confidence: 99%
“…Indeed, (Berezin, 2016d;Fazakas et al, 2016;Friedrich et al, 2013;Hofman et al, 2010;Kolder et al, 2012;McNamara et al, 2014;Sutter et al, 2013). As biomarkers particularly used to scrutiny single nucleotide polymorphisms (SNPs) of genes encoding enzymes related to oxidative stress (Berezin, 2016e), genotype of guanine nucleotide-binding proteins (G-proteins) beta-3 subunit (GNB3) (Fazakas et al, 2016), transcription factor Islet-1 gene (McNamara et al, 2014), troponin T (Friedrich et al, 2013), CYP2D6 polymorphism (Hofman et al, 2010), cardiac myosin binding protein-C mutations (Friedrich et al, 2013), renin-angiotensin-aldosterone system polymorphism (Sutter et al, 2013) etc. Indeed, it is well known that angiotensin-converting enzyme (ACE) I/D gene D allele was associated with higher overall mortality as compared with the I allele in HF patients and that the effect could be modified by ACE inhibitors' given (Kolder et al, 2012).…”
Section: Genetic Biomarkersmentioning
confidence: 99%